PENGARUH PENERAPAN METODE VAKT (VISUAL, AUDITORY, KINESTHETIC, TACTILE) TERHADAP PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS I SEKOLAH DASAR - Maspika, Sandi; Kurniawan, Wahyu (Universitas Islam Negeri Raden Intan Lampung, 2019)
ABSTRACTReading is the basic capabilities that must be mastered in order to understand the knowledge. In reality, not all children have a good reading skills. To overcome this problem researcher choosed VAKT method. Researcher believed toward VAKT method effective to improve literacy ability on early elementary school students. This study aimed to determine how the influence of VAKT methods to improve reading ability at the beginning of first grade elementary school students. The subject on this study was the first grade elementary school students. The subject on this study consist of 5 students. Experimental design used in this study is quasi experiment. The data analysed by nonparametric (Wilcoxon). The results showed that VAKT method effective to improve reading skills at the beginning of the first grade students of elementary school. The result showed that (z = -2.023, p= 0,043 (p <0.050). This study concluded that there was a significant difference between the ability to read at the beginning of the first grade students of elementary school before and after treatment. The reading ability at the beginning of the first grade students after the treatment is better than before the treatment. Key words: Implementation VAKT Method, Early Reading Ability